Microalgae : future bioresource of the sea? - Olofsson, Martin (Linnéuniversitetet, Institutionen för biologi och miljö (BOM), 2015)
Unicellular microalgae are a renewable bioresource that can meet the challenge forfood and energy in a growing world population. Using sunlight, CO2, nutrients,and water, algal cells produce biomass in the form of sugars, proteins and oils, allof which carry commercial value as food, feed and bioenergy. Flue gas CO2 andwastewater nutrients are inexpensive sources of carbon and fertilizers. Microalgaecan mitigate CO2 emissions and reduce nutrients from waste streams whileproducing valuable biomass.My focus was on some of the challenging aspects of cultivating microalgae ascrop: the response of biomass production and quality to seasonality, nutrients andbiological interactions. Approach spans from laboratory experiments to large-scaleoutdoor cultivation, using single microalgal strains and natural communities insouthern (Portugal) and northern (Sweden) Europe.Half of the seasonal variation in algal oil content was due to changes in light andtemperature in outdoor large-scale cultures of a commercial strain (Nannochloropsisoculata). Seasonal changes also influence algal oil composition with more neutrallipids stored in cells during high light and temperature. Nitrogen (N) stress usuallyenhances lipid storage but suppresses biomass production. Our manipulationshowed that N stress produced more lipids while retaining biomass. Thus,projecting annual biomass and oil yields requires accounting for both seasonalchanges and N stress to optimize lipid production in commercial applications.Baltic Sea microalgae proved to be a potential biological solution to reduce CO2emissions from cement flue gas with valuable biomass production. A multi-speciescultivation approach rather than single-species revealed that natural or constructedcommunities of microalgae can produce equivalent biomass quality. Diversecommunities of microalgae can offer resilience and stability due to more efficientresource utilization with less risk of contamination, less work and cost for culturemaintenance.Stable algal biomass production (annual basis) ...